The Civil Rights Movement in Dallas - Jones, Ian (My University, 2015)
The Civil Rights Movement was a defining movement in the United States of America and shaped the country as we know it today. Before the Montgomery Bus Boycotts, Rosa Parks, or Emmett Till, segregation in the southern states was a constant reminder of the inequalities that African-Americans had to endure. Traditionally Dallas, Texas has been a conservative city and was against the Civil Rights movement, but in the 1960s, we start to see the city shift towards being a progressive and desegregated area. The transition of Dallas, Texas from a conservative and segregated city to providing equality and guaranteeing African-Americans their Civil Rights is an area of history that has not been extensively studied. This transition was spearheaded by the actions of Mayor Earle Cabell (1961-1965), Juanita J. Craft (Civil Rights leader in Texas), Bob Cullum (grocery store owner), and Stanley Marcus (high end department store owner). These men and women greatly impacted the desegregation of Dallas and its communities. There was both opposition and support for Mayor Cabell's reforms and Craft, Cullum, and Marcus's push for desegregation, by comparing these reactions from the people of Dallas on both sides of the Civil Rights Movement one can gauge how the city was able to handle the Civil Rights Movement. One of the more surprising supporters of integration in Dallas were Cullum and Marcus, because they were wealthy white businessmen, but they played a key role in making Dallas a unique area of study in the Civil Rights Movement. Through studying and analyzing letters sent directly to Earle Cabell about desegregation, along with anti-segregation pamphlets, which compared desegregation to communist and anti-Christ ideals, one can see how the change in Dallas, Texas transitioned from a traditionally conservative city to a more progressive one. While there was certainly opposition to Mayor Cabell, Craft, Cullum, and Marcus, there were those who called for an end to segregation in the city both white and black.
Keywords: Civil rights movements -- United States -- History -- 20th century; Civil rights movements -- Texas -- History -- 20th century